A. J. Greimas’ Analysis in the Context of the French Structuralism - Venclova, Tomas (Problemos, 1974)
In his commentary “A. J. Greimas’ Analysis in the Context of the French Structuralism”, T. Venclova sheds light on the theoretical conditions under which A. J. Greimas’ ideas are developed and on the place of the published paper in the polemics of structuralists with their antagonists.